The Relationship Between GDP by Business Field and The Rate of Economic Growth Between Blora dan Bojonegoro Regencies - Adiseputra, Yudhistira; Adianita, Happy; Anggraeni, Anggun Nur (Universitas Gorontalo, 2025)
This study aims to analyze the comparison of GDP factors according to Business Fields that affect the economic growth rate of Bojonegoro and Blora Regencies. This study uses secondary and primary data. This study uses secondary data, namely Gross Regional Domestic Product (GDP) by Business Field on the basis of Constant Prices for the 2013-2023 Base Year, GDP, Secondary data sourced from BPS (Central Statistics Agency) of Bojonegoro and Blora Regencies. Data was obtained by documentation method. The data was processed using the Pearson Correlation Analysis technique using SPSS 20 to determine the strong or weak relationship between the 17 variables of the business sector (X) and the GDP variable (Y) of Bojonegoro and Blora Regencies. Overall, Blora Regency shows a better growth rate, citing stronger economic diversification and sectoral stability than Bojonegoro Regency. This puts Blora in a better position to achieve inclusive and sustainable growth in the long term. In 2022, Blora Regency's GDP (based on constant prices in 2010) grew by 2.68% overall. If the fluctuating contribution of the oil and gas sector is excluded, Blora's economic growth will reach 5.95%, which indicates healthier economic diversification. On the other hand, although Bojonegoro Regency's GDP was recorded to be larger in nominal terms, namely IDR 97.52 trillion in 2023, its economic growth only reached 2.47% overall, with the growth of the non-oil and gas sector at 5.17%.